1989
DOI: 10.1073/pnas.86.13.5114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin and activin modulate the release of gonadotropin-releasing hormone, human chorionic gonadotropin, and progesterone from cultured human placental cells.

Abstract: Although it is clear that human chorionic gonadotropin (hCG) and progesterone play fundamental roles in pregnancy, the regulation of placental production of these hormones remains to be defined. Recent evidence suggests that the human placenta expresses proteins related to inhibin (afi subunits) or activin (8P subunits). Inhibin and activin (folliclestimulating hormone-releasing protein) possess opposing activities in several biological systems including pituitary folliclestimulating hormone (follitropin) secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(69 citation statements)
references
References 32 publications
1
66
0
2
Order By: Relevance
“…Activin binds to ActRII or ActRIIB and the ligand receptor complex interacts with type I receptors Alk4 and possibly Alk2 leading to signal transduction (Attisano et al 1996). In situ studies have localised activin receptor ActRII and ActRIIB mRNA to the syncytium and amniotic epithelium (Petraglia et al 1994), consistent with the proposed roles for activin in both the regulation of placental secretion of various hormones, such as gonadotrophin hormone-releasing hormone, progesterone, human chorionic gonadotrophin (Petraglia et al 1989, Song et al 1996 and oestradiol (Ni et al 2000), and in the onset of parturition, as suggested by inducing prostaglandin release by the fetal membranes (Petraglia et al 1993b). However, we found only weak, sporadic receptor ActRIIB (also receptor Alk2 and ActRII) staining by immunohistochemistry in the trophoblast and amniotic epithelium which does not fully support a role for activin A in placental hormonogenesis or parturition in vivo in either healthy or preeclamptic women.…”
Section: Discussionmentioning
confidence: 73%
“…Activin binds to ActRII or ActRIIB and the ligand receptor complex interacts with type I receptors Alk4 and possibly Alk2 leading to signal transduction (Attisano et al 1996). In situ studies have localised activin receptor ActRII and ActRIIB mRNA to the syncytium and amniotic epithelium (Petraglia et al 1994), consistent with the proposed roles for activin in both the regulation of placental secretion of various hormones, such as gonadotrophin hormone-releasing hormone, progesterone, human chorionic gonadotrophin (Petraglia et al 1989, Song et al 1996 and oestradiol (Ni et al 2000), and in the onset of parturition, as suggested by inducing prostaglandin release by the fetal membranes (Petraglia et al 1993b). However, we found only weak, sporadic receptor ActRIIB (also receptor Alk2 and ActRII) staining by immunohistochemistry in the trophoblast and amniotic epithelium which does not fully support a role for activin A in placental hormonogenesis or parturition in vivo in either healthy or preeclamptic women.…”
Section: Discussionmentioning
confidence: 73%
“…Keelan et al Activin has been reported to exert a stimulatory effect on gonadotrophin-releasing hormone and hCG secretion from the placenta (37). Similarly, recent studies by Song et al (38) have shown that treatment of villous trophoblast cultures with activin A has a stimulatory effect on hCG production.…”
Section: Discussionmentioning
confidence: 93%
“…Although we have been unable to reproduce this finding, we have recently demonstrated an effect of activin A on prostaglandin E 2 production by amnion explants (Keelan et al 1999). Effects of activin on placental hormone production have been documented which may impact on the mechanism or timing of labour (Petraglia et al 1989, Florio et al 1995, Song et al 1996. Activin may also play hitherto unrecognised roles in the mechanism of parturition including local effects on cytokine function , Keelan et al 1999.…”
Section: Discussionmentioning
confidence: 99%